Valorization of fish from the Adriatic Sea: nutritional properties and shelf life prolongation of Aphia minuta through essential oils - Marino, Rosaria; Albenzio, Marzia; della Malva, Antonella; Racioppo, Angela; Speranza, Barbara; Bevilacqua, Antonio (Frontiers in Nutrition, 2024)
The aim of this study was to exploit the nutritional and microbiological quality of Aphia minuta, that are still unknown, collected from Golfo di Manfredonia (Adriatic Sea). Chemical composition, fatty acids and amino acids profile were evaluated during winter, spring and summer (two sampling for each season). The protein content was the highest in spring, while no significant differences were found for fat and ash contents during all sampling. The fatty acids profile analyses revealed that monounsatured and polyunsaturated fatty acids were affected by sampling season. Particularly, the value of n-3 polyunsaturated fatty acids increased in spring and summer compared to the winter season. The highest content of essential amino acids was measured during the spring and summer season (P< 0.01) with leucine and lysine being the most dominant. Regardless of the fishing season from nutritional point of view this specie is an excellent source of bioactive compounds.A focus on microbiological quality and shelf life of Aphia Minuta was also performed, first testing the bioactivity of three different essential oils (thymol, lemon, and citrus extract) on Pseudomonas fluorescens, Staphylococcus aureus and Escherichia coli and then combining EOs through packaging material (conventional, maize starch, and poly lactate) and packaging atmosphere (air, vacuum, and a modified atmosphere with a reduced content of oxygen). The results pointed out a strong effect of the combination of citrus extract with packaging under vacuum, with a gradual reduction of psychrotrophic viable count to the undetectable level after 7 days.This study suggests some important considerations for to exploit and expand the market of the Aphia minuta.